Good Corporate Governance Mechanisms, Company Size, and Company’s Growth On Company's Financial Performance - Endang Kurniati; Ilham Hidayah Napitupulu; Lovhian Simamora; Akmal Hidayat (Jurnal ASET (Akuntansi Riset), 2024)
This study aims to determine the effect of independent commissioners, board of directors, company size, and company growth on the company's financial performance. Financial performance is a description of the company's financial condition in a certain period of time. Financial performance in this study uses the ratio of return on assets. This research uses a purposive sampling technique, the number of samples obtained was 31 companies from 81 property and real estate companies listed on the IDX. Research data was obtained from the company’s financial reports for the 2016-2021 period, and the data was analyzed using multiple linear regression analysis assisted by the SPSS application. The results of this research show that Independent Commissioners, Company Size, and Company Growth affect the company's Financial Performance, while the Board of Directors has does not affect Financial Performance. The greater the proportion of independent commissioners, the higher the supervision, meanwhile the number of the board of directors has no effect on financial performance, this is because a board of directors that is too large cannot function optimally because it will have difficulty coordinating. A decline in financial performance can be caused by enormous asset maintenance costs and a company's large operational scope, a decline or increase in performance seen from the company's profits, where profits increase due to sales growth and lower costs. This research has implications for stakeholder theory and Agency theory, because good corporate governance provides benefits to interested parties in the company. In implementing good corporate governance, a large number of board of directors also has an unfavorable effect because the larger the number of the board of directors has an impact on communication and coordination, as well as the higher the hierarchy of task implementation within the company.